Neural Networks, ARIMA and ARIMAX Models for Forecasting Indonesian Inflation - Suhartono, . (Jurnal Widya Manajemen & Akuntansi, 2005)
The objective of this study is to apply Neural Networks (NN) model for forecasting Indonesian inflation and to compore a result with ARIMA ond ARIMAX models. The Feedforward Neural Networks model used for forecasting, particularly in economics and finance.